Serum ferritin as a prognostic marker in acute stroke; a cross-sectional observational study - Mohan, Nidin; Murthy, Karthick; Yoganandan, Dayanandan; Rajalakshmi, Kandasamy Venkatraju; Kumar, S. Magesh (International Journal of Advances in Medicine, 2022)
Background: Stroke is the leading cause of morbidity and mortality all over the world. Several prognostic factors like site and size of infarction, Glasgow coma scale, level of cerebral edema, intracranial tension have been found significant in stroke. Among the prognostic indicators ferritin has gained importance in recent times. It is considered an acute phase reactant and has been used for assessing the severity and prognosis of stroke. Aim of the study was to correlate the levels of serum ferritin with early neurological status and to predict the severity and prognosis earlier in patients of acute stroke. Methods: This cross-sectional observational study was done in Saveetha hospital, Chennai. Clinically diagnosed CVA patients within 48 hours of the onset of symptoms were recruited in this study. 122 patients above 18 years who fulfilled the criteria were included and patients with a recent history of inflammation, malignancy, and anemia were excluded. Results: Around 60.7% of patients had improved and the remaining of them deteriorated. The level of serum ferritin was well correlated with the patient's prognosis. Those who deteriorated had high serum ferritin when compared to those who improved and it was statistically significant. Conclusions: From our results, we concluded that patients with increased ferritin concentrations have a higher risk of poor clinical outcomes. These findings suggest that iron overload may counterbalance the benefits of thrombolytic therapy in patients with high ferritin levels. Therefore, serum ferritin can be used as a prognostic marker for assessing the severity and prognosis of stroke.